Chondrosarcoma of the hyoid bone: an atypical site of a sarcoma of the head and the neck. (5th November 2015) - Horta, Mariana; Fernandes, Leonor; Borges, Alexandra
Abstract : We describe a case of a 73-year-old man with a chondrosarcoma of the hyoid bone. The patient presented with a painless palpable lump in the upper anterior cervical region that had been growing for over 10 months. Fine-needle aspiration cytology suggested pleomorphic adenoma but further imaging investigation with CT revealed an exophytic tumour originating from the body of the hyoid bone with prominent chondroid-like calcifications typical of a chondrosarcoma. Histopathology of the surgical specimen confirmed the diagnosis of a moderately differentiated chondrosarcoma. Chondrosarcomas account for 11% of all bone cancers, of which up to 12% are in the head and neck. Primary sites of the head and the neck include the skull base, the nasal cavity, the maxilla, the mandible and the larynx. Chondrosarcomas of the hyoid bone are exceptionally rare, with only 20 such cases previously reported in the English literature.